Influence of Organizational Culture, Work Ethics, and Competence on Employee Performance at LPP RRI Surabaya - Ericha Fitrianingsih; Siti Mujanah; Snyder Bradford (Yayasan Adra Karima Hubbi, 2023)
The purpose of this study was to analyze the effect of organizational culture, work ethics, and competence on employee performance at LPP RRI Surabaya. This research was conducted at Radio Republik Indonesia Surabaya (RRI Surabaya), which is a radio station owned by LPP Radio Republik Indonesia in Surabaya City, East Java. This study uses a quantitative approach to see the relationship between the independent variables and the dependent variable, this study applies samples and hypotheses. The sample applied was 50 employees of LPP RRI Surabaya using the saturated sampling technique method. The data analysis technique applied is multiple linear regression including test instrument validity and reliability tests. In testing the hypothesis apply a partial test (t test) and simultaneous test (f test). The results of the study show that organizational culture partially does not have a significant effect on the performance of LPP RRI Surabaya employees, work ethics have a significant effect on the performance of LPP RRI Surabaya employees, and competence has a significant effect on the performance of LPP RRI Surabaya employees. Simultaneously the variables of organizational culture, work ethics, and competence have a significant influence on employee performance at LPP RRI Surabaya.